VISUALISASI LIRIK LAGU “LIR ILIR” UNTUK ANAK-ANAK BERBASIS METODE DOUBLE DIAMOND - Abi Senoprabowo; Altius Jordan; Ryan Mujianto (Jurnal Pendidikan Seni dan Industri Kreatif, 2021)
“Lir Ilir”, a folk song composed by Sunan Kalijaga, contains righteous meaning that teaches life lessons to human beings. The development of technology and information at the present time has triggered Indonesian children to be closer to and familiar with foreign cultures which may bring about negative impact on the preservation of Indonesian culture. Indonesian children become more familiar with foreign language songs rather than with Indonesian folk songs. Accordingly, the values of local culture may diminish over time when children tend to appreciate other cultures than their own one. The current study aims to create a visualization design of the lyrics of “Lir Ilir” as a complementary media of recognizing folk song to appeal mainly to children. The study employs Double Diamond design method approach. At the development phase, the cost-benefit matrix is used as a validation tool. The study results in four illustration posters employing the illustration styles of realistic, cute childlike, and spread illustrations in accordance with parts of stanzas in “Lir Ilir” lyrics. The visualization design of “Lir Ilir” may help Indonesian children to recognize, understand, and interpret the values of local cultures in Indonesia. Lyrics of Lir Ilir is one of the examples providing this purpose.